Penerapan Model Pembelajaran Berbasis TIK Bagi Guru-Guru SMP Swasta Islam Tahfidz - Zulkarnain Sirait; Guntur Maha Putra; Akmal Akmal (Ali Institute of Research and Publication, 2021)
The application of learning models is one of the means to support the achievement of learning implementation, by using a structured and orderly way to be delivered to students. The development of learning models is also an effort from a teacher to achieve the goal of a discussion on the material to be conveyed so that it is lighter and easier for students to understand. Developments in modernity today are information and communication technology, the development of all aspects can be obtained through technology. Technology is used as a learning model in a more modern and innovative world of education. One of the applications used in the Information and Communication Technology (ICT) based learning model is Google Classroom which can make students easily access all sources of learning information, therefore information and communication technology can make it easier for teachers and students to find and explore information. various sciences.